Effect of Different Levels of Multienzymes on Immune Response, Blood Hematology and Biochemistry, Antioxidants Status and Organs Histology of Broiler Chicks Fed Standard and Low-Density Diets - Attia, Y. A.; Al-Khalaifah, H.; Abd El-Hamid, H. S.; Al-Harthi, M. A.; El-shafey, A. A. (Frontiers in Veterinary Science, 2020)
This study was executed to investigate the effect of supplementing three multienzyme levels (0, 0. 1, and 0.2%) with two types of diet [standard diet (SD) vs. low-density diet (LDD)] on immune response, blood hematology and biochemistry, antioxidant status, and organ histology of broilers during 1–38 days of age. A total of 216 unsexed 1-day-old Arbor Acres broiler chicks were randomly distributed, on a factorial design (2 × 3), to six treatments each with six replicates. There were six chicks per replicate. Results showed that LDD significantly decreased body weight gain (BWG) of broilers, but did not affect the European Production Efficiency Index (EPEI). Addition of multienzymes at both levels (0.1 and 0.2%) significantly increased BWG and improved EPEI, compared to the control diet. Alanine aminotransferase (ALT), aspirate aminotransferase (AST), malondialdehyde (MDA), lymphocyte, lymphocyte transformation test (LTT), and phagocyte activity (PA) were significantly higher for LDD than the SD, but eosinophil was lower. Supplementation of multienzymes significantly decreased ALT, AST, and MDA, compared to the control group, but increased packed cell volume (PCV), hemoglobin (Hgb), lymphocytes, and monocytes. Immune organs, such as spleen, thymus, and the bursa of Fabricius were significantly increased with multienzyme supplementation. It could be concluded that multienzyme supplementation at either 0.1 or 0.2% to SD or LDD improved EPEI and immune status of broiler chicks.